An analysis of three dimensional changes to comprehensively evaluate the occlusion time, disclusion time, point of first contact and force distribution at various head positions using Tekscan III: An in vivo study - G. S. Prasanthi; M. C. Suresh Sajjan; Yenumula J. B. Manikyamba; P. V. B. Chandrasekhar; Sri Lakshmi Kotemsetty (Wolters Kluwer Medknow Publications, 2024)
Aim: This study aims to evaluate the changes in occlusal contacts resulting from variations in head postures (supine[S], semi-supine [SS], upright with head rest support [HR], and without head rest support [WHR]) after occlusal adjustment of conventional fixed dental prostheses using Tekscan III. Settings and Design: A cross-sectional study on 15 patients with missing single molars and undergone replacement with a fixed dental prosthesis. Materials and Methods: Fifteen patients with a three-unit tooth-supported fixed dental prosthesis replacing a missing single posterior tooth were included. Tekscan III was used to analyze occlusion time (OT), disclusion time (DT), initial tooth contact, and relative bite force in different head postures by adjusting the backrest position before and after equilibration. Occlusal adjustments were performed to achieve the balance between the right and left halves. Statistical Analysis Used: The data were statistically analyzed using ANOVA and paired t-test. Results: Posterior shift of initial tooth contact was observed from SS to supine and upright positions, whereas an anterior shift occurred from SS to WHR support posture. High-intensity forces were observed before the occlusal adjustment in various head positions, and these forces changed after adjustments in SS position. However, medium-intensity force occlusal prematurities persisted in other head postures even after corrections in SS position. There was a significant difference in OT but not in DT in all head postures after equilibration. When OT was compared from SS to remaining posture after equilibration, the major difference was found from SS to head rest (HR) and supine to HR posture which infers the need for selective grinding in these postures. Conclusion: Considering the various changes while changing the head position from the SS position to the other functional position, it can be inferred that there is a need to consider recalibration of occlusal contacts in all the functional postures.